EVALUATION OF THE PERCEPTIONS OF "CIVILIANIZATION” IN TEACHER CANDIDATES - Rüştü YEŞİL (Fırat University, 2019)
In our research, it is aimed to investigate the mediating role of college students' intrinsic and extrinsic life purpose related to their hopes and psychological well-being. The study has been carried out with 511 university students including 269 (52.6%) women and 242 (47.4%) men that have studied at different faculties of a state university in Turkey. “The Domain Specific Hope Scale” developed by Sympson (1999) and adapted to Turkish by Özbay, Terzi and Aydoğan (2011); “Psychological Well-being Scale” developed by Diener and his colleagues (2009, 2010) and adapted into Turkish by Telef (2011; 2013) and “Life Purpose Scale” developed by İlhan (2009) have been used. The technique as regression-based mediator macro which has been offered by Preacher ve Hayes (2008), has been used to determine the mediating role of intrinsic and extrinsic life purpose in the relationship between hope and psychological well-being. Sobel Z and bootstrapping have been used in evaluating the indirect effects. Descriptive statistics of variables were determined before mediation tests, and correlations between variables were analyzed by Pearson’s Product-Moments Correlation analysis. When we look at correlational findings, moderate positive relationships have been found between psychological well-being and hope and intrinsic, extrinsic life purpose. Nevertheless, it has been determined that both of intrinsic and extrinsic life purpose are significant predictors of psychological well-being. According to mediating results it has been found that both of intrinsic and extrinsic life purpose have mediated the relationship between hope and psychological well-being partially. As a result, it can be said that an increase in students' hopes increases their intrinsic and extrinsic life purpose, and with this increase their psychological well-being can be strengthened.